2015
DOI: 10.1016/j.eucr.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome After Robotically Assisted Laparoscopic Prostatectomy: First Case Report

Abstract: Guillain-Barre Syndrome is a well described acute demyelinating polyradiculoneuropathy with a likely autoimmune basis characterized by progressive ascending muscle paralysis. Classically, GBS is attributed to antecedent upper respiratory and gastrointestinal infections. We present the first case of GBS after Robotically Assisted Laparoscopic Prostatectomy using the daVinci® Surgical System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition, non-infectious factors such as vaccinations, trauma, and surgery have been reported as possible triggers of GBS. Several case reports have also described the occurrence of GBS following cardiac surgery, gastrointestinal surgery, neurological surgery, orthopedic surgery, and laparoscopic prostatectomy [ 3 15 ]. Gensicke et al reported that the incidence of GBS after surgery was significantly higher than for GBS triggered by infection or vaccine [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, non-infectious factors such as vaccinations, trauma, and surgery have been reported as possible triggers of GBS. Several case reports have also described the occurrence of GBS following cardiac surgery, gastrointestinal surgery, neurological surgery, orthopedic surgery, and laparoscopic prostatectomy [ 3 15 ]. Gensicke et al reported that the incidence of GBS after surgery was significantly higher than for GBS triggered by infection or vaccine [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, non-infectious factors such as vaccinations, trauma and surgery were reported as possible triggers. Several case reports described the occurrence of GBS following cardiac surgery, gastrointestinal surgery, neurological surgery, orthopedic surgery, laparoscopic prostatectomy, and so on [3][4][5][6][7][8][9][10][11][12][13][14][15] . H. Gensicke et al found that the Hughes Functional Grading Scale (HFGS) score [24] , a widely accepted scale of disability for GBS (Grade 0, healthy; grade 1, minor signs or symptoms of neuropathy but capable of manual work; grade 2, able to walk without support of a stick but incapable of manual work; grade 3, able to walk with a stick, appliance, or support; grade 4, con ned to bed or chair bound; grade 5, requiring assisted ventilation; grade 6, dead) was applied.…”
Section: Introductionmentioning
confidence: 99%